Edgar Allan Poe in context - Hayes, Kevin J. (Cambridge University Press, 2013)
Edgar Allan Poe mastered a variety of literary forms over the course of his brief and turbulent career. As a storyteller, Poe defied convention by creating Gothic tales of mystery, horror and suspense that remain widely popular today. This collection demonstrates how Poe's experience of early nineteenth-century American life fueled his iconoclasm and shaped his literary legacy. Rather than provide critical explications of his writings, each essay explores one aspect of Poe's immediate environment, using pertinent writings - verse, fiction, reviews and essays - to suit. Examining his geographical, social and literary contexts, as well as those created by the publishing industry and advances in science and technology, the essays paint an unprecedented portrait of Poe's life and times. Written for a wide audience, the collection will offer scholars and students of American literature, historians and general readers new insight into Poe's rich and complex work.
Keywords: Poe, Edgar Allan, : 1809-1849 : Criticism and interpretation